Design and Development of an Internet of Things (IoT)-Based Real-Time Tide Monitoring System for Coastal Water Level Observation - Muhammad Ari Juanda; Mhd. Basri (Hanif Journal of Information Systems, 2026)
Sea tides are a phenomenon of the periodic rise and fall of sea level caused by a combination of gravitational force and the attractive force of astronomical objects, especially the sun, earth and moon. Every day the tidal phenomenon occurs and information about tides is very useful for human activities related to the marine sector such as fishing and other activities. There is a need for intelligent tool concept technology that can help and alleviate this problem, so an instrumentation tool has been created that can provide tidal information at any time that can be accessed via the internet network using the Android system. Decisions can match human thought patterns. The electronic components used in implementing the system are nodeMCU as a controller and internet of things (IOT) communication, ultrasonic sensors function as a medium for measuring sea water height. This research produces a system that can monitor the ebb and flow of sea water. In the system, a notification system is implemented for system users so they can monitor the ebb and flow of sea water. The application used is the blynk application which is integrated with the internet.